Thrombelastogram are associated with coronary artery aneurysm in Kawasaki disease patients - Yue Peng; Jinhui Wu; Xue Zhou; Ya Su (BMC Cardiovascular Disorders)
Abstract Background Kawasaki disease (KD) is a common pediatric disease that readily affects the coronary arteries and can progress to form coronary artery aneurysms (CAA). This study aimed to explore the relationship between thromboelastography MA and CAA and to ascertain whether thromboelastography MA could act as a predictor of CAA in KD patients. Methods A total of 243 consecutive KD patients from January 2020 to December 2022 were included in this study. Differences in baseline characteristics were compared through analysis, and subsequent multivariable logistic regression analysis was performed to identify independent risk factors for CAA in KD patients. Results Among the 243 KD patients, 107 were female and 136 were male, with a median age of 23 months. Differential analysis indicated that the R, K, α, gender, WBC, HB, PLT and NLR were not significantly different, but the MA, age, IVIG resistance, CRP and albumin were significantly different between the KD-CAA and the KD-NCAA groups. Subsequent multivariable logistic regression analysis showed that age (Adjusted OR 0.988; 95% CI, 0.977–0.999; P = 0.039), albumin (Adjusted OR 0.902; 95% CI, 0.852–0.956; P < 0.001) and MA (Adjusted OR 1.846; 95% CI, 1.069–3.187; P = 0.028) were independently associated with CAA in KD patients. Conclusion Thromboelastography MA is closely related to CAA and may be a predictor of CAA in KD patients.